Domestic Tourism in Jordan: Patterns, Challenges and Opportunities - ALZBOUN, Nidal Mohammed (Journal of Environmental Management and Tourism, 2019)
The present study sought to explore the characteristics of domestic tourists in Jordan in terms of patterns, motivations, challenges and opportunities. A sample of 556 residents was collected through online survey technique. The quantitative approach was employed to analyze the data. The results indicated that coastal tourism beside adventure tourism and curatives tourism are the major patterns of domestic tourism. The main challenges of domestic tourism are related to economic, services, and socio-cultural aspects respectively. The results from One-Way ANOVA and t-tests revealed that there are no signiﬁcant differences in respondents’ perceptions between demographic groups in terms of age, gender, income, car ownership, and level of education for challenges of domestic tourism. Moreover, possible opportunities could be generated through involving private sector in promotional campaigns for the least known destinations, encouraging investment at small and medium accommodation enterprises with reasonable prices, and increasing the level of awareness for local community toward domestic tourism .